Preparation method of graphite negative electrode material and graphite negative electrode material
By mixing aromatic oil, thiophene with medium and high sulfur asphalt and heat treatment and delayed coking, graphite negative electrode materials with large graphite layer spacing and small grain size were prepared, which solves the improvement of rate performance in the prior art with deterioration of high-temperature storage performance in the existing technology The problem of this is to achieve efficient rate performance and high-temperature storage performance.
Patent Information
- Application Number
- CN202411530325.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-11
AI Technical Summary
The prior art has the problem of deteriorating the high-temperature storage performance when improving the rate performance of graphite negative electrodes.
By mixing aromatic oil, thiophene with medium and high sulfur asphalt and heat treatment, vulcanized asphalt was obtained, and then graphitized after delayed coking and crushing were performed to prepare graphite negative electrode material with large graphite layer spacing and small grain size.
It significantly improves the rate performance of graphite negative electrode, while maintaining good high-temperature storage performance, and the preparation method is simple, low cost and high economic benefits.
Smart Images

Figure BDA0005110324200000151 
Figure BDA0005110324200000161
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and specifically provides a method for preparing a graphite negative electrode material and a graphite negative electrode material. Background Art
[0002] As an advanced portable energy storage system, lithium-ion batteries (LIBs) have driven the rapid development of electric vehicles (EVs) in the past few years. Compared with gasoline vehicles (GCs), EVs are more environmentally friendly, energy-efficient and economical. However, a prominent disadvantage of current EVs is that the waiting time for the battery to be charged from an empty state to a full state is long, while refueling a gasoline vehicle only takes a few minutes. Therefore, the terminal market has put forward higher requirements for the rate performance of power lithium-ion batteries to ensure the large-scale application of EVs.
[0003] At present, the negative electrode materials that have been applied on a large scale in lithium-ion batteries are mainly natural graphite and artificial graphite. Artificial graphite has better performance than natural graphite, and its share in the negative electrode material application market of lithium-ion batteries has increased year by year. Since the average working potential of graphite embedded with lithium is about 0.1V, it is easy for the graphite negative electrode to precipitate lithium when the lithium battery is charged at a high rate, causing serious safety hazards. Therefore, how to improve the rate performance of graphite negative electrodes has become an urgent problem that needs to be solved.
[0004] At present, conventional modification methods for improving the rate performance of graphite negative electrodes include asphalt coating. Asphalt coating is to mix, coat and carbonize asphalt with graphite negative electrode materials to obtain graphite negative electrode materials coated with surface amorphous carbon to improve their rate performance. However, the surface-coated amorphous carbon has high chemical activity, which is easy to increase the side reactions on the negative electrode surface and deteriorate the high-temperature storage performance. Accordingly, a new technical solution is needed in this field to solve the above technical problems. Summary of the invention
[0005] The present application aims to solve the above technical problem, that is, to solve the problem that the existing method for improving the rate performance of graphite negative electrode deteriorates the high temperature storage performance.
[0006] In a first aspect, the present application provides a method for preparing a graphite negative electrode material, the preparation method comprising the following steps: S1: mixing aromatic oil, thiophene and medium-high sulfur asphalt, and heat treating to obtain sulfided asphalt; S2: delaying coking the sulfided asphalt to obtain high-sulfur green coke; S3: crushing the high-sulfur green coke, and then graphitizing it to obtain a graphite negative electrode material.
[0007] In the preferred technical solution of the method for preparing the above-mentioned graphite negative electrode material, the sulfur content in the medium-high sulfur asphalt is 2.5% to 5%, and the softening point of the medium-high sulfur asphalt is 50°C to 80°C.
[0008] In the preferred technical scheme of the preparation method of the above-mentioned graphite negative electrode material, in step S1, the aromatic oil, the thiophene and the medium-high sulfur asphalt are added according to the following weight proportions: 15-20 parts of aromatic oil, 1-6 parts of thiophene, and 76-83 parts of medium-high sulfur asphalt.
[0009] In the preferred technical solution of the above-mentioned method for preparing the graphite negative electrode material, in step S1, the weight proportion of thiophene is 2 to 4 parts.
[0010] In the preferred technical solution of the method for preparing the above graphite negative electrode material, in step S1, the temperature of the heat treatment is 120°C to 160°C.
[0011] In the preferred technical scheme of the preparation method of the above-mentioned graphite negative electrode material, step S2 specifically includes: S21: polymerizing the sulfide asphalt at a temperature of 400°C to 480°C and a pressure of 0.1MPa to 0.25MPa to obtain a polymer intermediate; S22: coking the polymer intermediate at 500°C to 600°C to obtain high-sulfur raw coke.
[0012] In the preferred technical solution of the method for preparing the above-mentioned graphite negative electrode material, in step S21, the polymerization time is 5h to 7h; and / or, in step S22, the coking reaction time is 16h to 20h.
[0013] In the preferred technical scheme of the preparation method of the above-mentioned graphite negative electrode material, in step S3, the particle size of the high-sulfur raw coke after crushing is D50=9.0μm~12.0μm and / or, in step S3, the temperature of the graphitization treatment is 2800℃~3000℃.
[0014] In a second aspect, the present application provides a graphite negative electrode material, which is prepared by the above-mentioned method for preparing the graphite negative electrode material.
[0015] In the preferred technical solution of the above graphite negative electrode material, the graphite layer spacing of the graphite negative electrode material is 0.3360nm to 0.3364nm, and the grain size Lc of the graphite negative electrode material is 20.0nm to 32.0nm.
[0016] Compared with the prior art, the preparation method of the graphite negative electrode material of the present application has the following advantages: Beneficial effects:
[0017] The preparation method of the graphite negative electrode material of the present application adds thiophene at the stage of heat treating medium-high sulfur asphalt to form sulfurized asphalt, so that the obtained high-sulfur green coke has a higher content of thiophene, so that in the subsequent graphitization process, thiophene will decompose at high temperature (greater than 1500°C) and continue to decompose and overflow, so that the finally prepared graphite negative electrode material has a larger graphite layer spacing and a smaller grain size, and at the same time has a rich pore structure, which can significantly improve the rate performance of the graphite negative electrode.
[0018] In addition, compared with conventional asphalt coating or doping modification, the preparation method of the present application is simple, and medium-high sulfur asphalt is selected as raw material, which has low cost and high economic benefit, and the obtained graphite negative electrode material has good rate performance and high-temperature storage performance when applied to lithium batteries. DETAILED DESCRIPTION
[0019] The preferred embodiments of the present application are described below. It should be understood by those skilled in the art that these embodiments are only used to explain the technical principles of the present application and are not intended to limit the protection scope of the present application.
[0020] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0021] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0022] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0023] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0024] The experimental methods in the following examples are conventional methods unless otherwise specified, and the materials, reagents, etc. used in the following examples are commercially available unless otherwise specified.
[0025] The existing method for improving the rate performance of graphite negative electrodes proposed in the background art has the problem of deteriorating high-temperature storage performance.
[0026] The present application provides a method for preparing a graphite negative electrode material, wherein thiophene is added during the stage of heat treating medium-high sulfur asphalt to form sulfurized asphalt, so that the obtained high-sulfur raw coke has a higher content of thiophene, so that in the subsequent graphitization process, thiophene will decompose at high temperature (greater than 1500°C) and continuously decompose and overflow, so that the finally prepared graphite negative electrode material has a larger graphite interlayer spacing and a smaller grain size, and has a rich pore structure, which can significantly improve the rate performance of the graphite negative electrode. In addition, compared with conventional coating or doping modification, the preparation method of the present application is simple, and medium-high sulfur asphalt is selected as the raw material, which has low cost and high economic benefits, and the obtained graphite negative electrode material is applied to lithium batteries with good rate performance and high temperature storage performance.
[0027] Specifically, the method for preparing the graphite negative electrode material of the present application comprises the following steps:
[0028] S1: Aromatic oil, thiophene and medium-high sulfur asphalt are mixed and heat treated to obtain sulfided asphalt.
[0029] S2: Delay coking of the sulfided asphalt to obtain high-sulfur raw coke.
[0030] S3: The high-sulfur raw coke is crushed and then graphitized to obtain a graphite negative electrode material.
[0031] The preparation method of the graphite negative electrode material of the present application uses medium-high sulfur asphalt as raw material, aromatic oil as solvent, adds thiophene and then performs heat treatment to obtain sulfided asphalt, so that the sulfided asphalt contains thiophene, and then the sulfided asphalt is delayed coked so that the obtained high-sulfur green coke has a certain content of thiophene, and then the high-sulfur green coke is crushed and graphitized to obtain a graphite negative electrode material with a large graphite interlayer spacing and a small grain size. During the graphitization process, thiophene will decompose at high temperature (greater than 1500°C) and continuously decompose and overflow, so that the finally prepared graphite negative electrode material has a large graphite interlayer spacing and a rich pore structure, which can significantly improve the rate performance of the graphite negative electrode, and also has good high-temperature storage performance.
[0032] In addition, compared with conventional coating or doping modification, the preparation method of the present application is simple, and medium-high sulfur asphalt is selected as the raw material, which has low cost and high economic benefit, and the obtained graphite negative electrode material has good rate performance and high-temperature storage performance when applied to lithium batteries.
[0033] Preferably, the sulfur content in the medium-high sulfur asphalt is 2.5% to 5%, and the softening point temperature of the medium-high sulfur asphalt is 50°C to 80°C.
[0034] It should be noted that the medium-high sulfur asphalt in this application refers to sulfur asphalt with a sulfur content in the range of 2.5% to 5%. The medium-high sulfur asphalt in this sulfur content range may produce fewer pollutants during processing, and has low production requirements, thereby reducing processing and use costs, thereby reducing costs and having higher economic benefits. The softening point temperature of the medium-high sulfur asphalt is 50°C to 80°C, which is convenient for production and use, and the performance of the obtained graphite negative electrode material is good.
[0035] Preferably, in step S1, aromatic oil, thiophene and medium-high sulfur asphalt are added according to the following weight proportions: 15-20 parts of aromatic oil, 1-6 parts of thiophene, and 76-83 parts of medium-high sulfur asphalt; further, the weight proportion of thiophene is 2-4 parts.
[0036] In specific use, the addition amount of aromatic oil is controlled to be 15-20 parts. Optionally, the weight proportion of aromatic oil is 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts or a value within the range composed of any of the above values.
[0037] In specific use, the amount of thiophene added is controlled to be 1 to 6 parts, and optionally, the weight of thiophene is 1 part, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 5 parts, 6 parts or any value within the range of the above values. Of course, it is preferred that the weight of thiophene is 2 to 4 parts.
[0038] In specific use, the addition amount of medium-high sulfur asphalt is controlled to be 76 to 83 parts. Optionally, the weight proportion of medium-high sulfur asphalt is 76 parts, 77 parts, 78 parts, 79 parts, 80 parts, 81 parts, 82 parts, 83 parts or a value within the range composed of any of the above values.
[0039] By controlling the amount of aromatic oil, thiophene and medium- and high-sulfur asphalt, the interlayer spacing, pore structure and grain size of the prepared graphite negative electrode material can be effectively guaranteed, thereby improving the performance of the graphite negative electrode.
[0040] Preferably, in step S1, the temperature of the heat treatment is 120°C to 160°C.
[0041] Preferably, step S2 specifically includes:
[0042] S21: polymerizing the sulfided asphalt at a temperature of 400° C. to 480° C. and a pressure of 0.1 to 0.25 MPa to obtain a polymer intermediate.
[0043] S22: The polymer intermediate is subjected to a coking reaction at 500-600° C. to obtain high-sulfur raw coke.
[0044] Preferably, in step S21, the polymerization time is 5 h to 7 h.
[0045] Preferably, in step S22, the coking reaction time is 16 h to 20 h.
[0046] Preferably, in step S3, the particle size of the high-sulfur green coke after crushing is D50=9.0-12.0 μm.
[0047] Preferably, in step S3, the temperature of the graphitization treatment is 2800°C to 3000°C.
[0048] In a second aspect, the present application provides a graphite negative electrode material, which is prepared by the preparation method of the graphite negative electrode material provided by the first aspect, the graphite layer spacing of the graphite negative electrode material is 0.3360~0.3364nm, and the grain size Lc of the graphite negative electrode material is 20.0nm~32.0nm.
[0049] The graphite negative electrode material prepared by the preparation method of the graphite negative electrode material of the present application has a graphite interlayer spacing of 0.3360~0.3364nm, a grain size Lc of the graphite negative electrode material of 20.0nm~32.0nm, a large graphite interlayer spacing, a rich pore structure and a small grain size, which can effectively improve the performance of the graphite negative electrode material. The graphite negative electrode material is applied to lithium batteries, which can effectively improve the rate performance of the graphite negative electrode and has good high-temperature storage performance.
[0050] The preparation method of the graphite negative electrode material and the graphite negative electrode material of the present application are described in detail below through several specific embodiments.
[0051] Example 1
[0052] A graphite negative electrode material is prepared by the following steps:
[0053] S1: 80 parts of medium-high sulfur asphalt, 17 parts of aromatic oil, and 3 parts of thiophene are mixed and heat-treated at 130°C to obtain sulfided asphalt. The sulfur content of the medium-high sulfur asphalt is 3% and the softening point is 50°C.
[0054] S2: The sulfide asphalt is polymerized at a temperature of 450°C and a pressure of 0.2 MPa for 5 hours to obtain a polymerization intermediate; the polymerization intermediate is then coked at 500°C to obtain high-sulfur raw coke.
[0055] S3: The high-sulfur raw coke is crushed to a particle size of D50=10.0 μm, and then graphitized at 2800° C. to obtain a graphite negative electrode material.
[0056] Example 2
[0057] A graphite negative electrode material is prepared by the following steps:
[0058] S1: 76 parts of medium-high sulfur asphalt, 15 parts of aromatic oil, and 2 parts of thiophene are mixed and heat-treated at 130°C to obtain sulfided asphalt. The sulfur content of the medium-high sulfur asphalt is 3% and the softening point is 50°C.
[0059] S2: The sulfide asphalt is polymerized at a temperature of 450°C and a pressure of 0.2 MPa for 5 hours to obtain a polymerization intermediate; the polymerization intermediate is then coked at 500°C to obtain high-sulfur raw coke.
[0060] S3: The high-sulfur raw coke is crushed to a particle size of D50=10.0 μm, and then graphitized at 2800° C. to obtain a graphite negative electrode material.
[0061] Example 3
[0062] A graphite negative electrode material is prepared by the following steps:
[0063] S1: 83 parts of medium-high sulfur asphalt, 20 parts of aromatic oil, and 4 parts of thiophene are mixed and heat-treated at 130°C to obtain sulfided asphalt. The sulfur content of the medium-high sulfur asphalt is 3% and the softening point is 50°C.
[0064] S2: The sulfide asphalt is polymerized at a temperature of 450°C and a pressure of 0.2 MPa for 5 hours to obtain a polymerization intermediate; the polymerization intermediate is then coked at 500°C to obtain high-sulfur raw coke.
[0065] S3: The high-sulfur raw coke is crushed to a particle size of D50=10.0 μm, and then graphitized at 2800° C. to obtain a graphite negative electrode material.
[0066] Example 4
[0067] A graphite negative electrode material is prepared by the following steps:
[0068] S1: 80 parts of medium-high sulfur asphalt, 17 parts of aromatic oil and 1 part of thiophene are mixed and heat-treated at 130°C to obtain sulfided asphalt. The sulfur content of the medium-high sulfur asphalt is 3% and the softening point is 50°C.
[0069] S2: The sulfide asphalt is polymerized at a temperature of 450°C and a pressure of 0.2 MPa for 5 hours to obtain a polymerization intermediate; the polymerization intermediate is then coked at 500°C to obtain high-sulfur raw coke.
[0070] S3: The high-sulfur raw coke is crushed to a particle size of D50=10.0 μm, and then graphitized at 2800° C. to obtain a graphite negative electrode material.
[0071] Example 5
[0072] A graphite negative electrode material is prepared by the following steps:
[0073] S1: 80 parts of medium-high sulfur asphalt, 17 parts of aromatic oil, and 6 parts of thiophene are mixed and heat-treated at 130°C to obtain sulfided asphalt. The sulfur content of the medium-high sulfur asphalt is 3% and the softening point is 50°C.
[0074] S2: The sulfide asphalt is polymerized at a temperature of 450°C and a pressure of 0.2 MPa for 5 hours to obtain a polymerization intermediate; the polymerization intermediate is then coked at 500°C to obtain high-sulfur raw coke.
[0075] S3: The high-sulfur raw coke is crushed to a particle size of D50=10.0 μm, and then graphitized at 2800° C. to obtain a graphite negative electrode material.
[0076] Example 6
[0077] A graphite negative electrode material is prepared by the following steps:
[0078] S1: 80 parts of medium-high sulfur asphalt, 17 parts of aromatic oil, and 3 parts of thiophene are mixed and heat-treated at 130°C to obtain sulfided asphalt. The sulfur content of the medium-high sulfur asphalt is 2.5% and the softening point is 50°C.
[0079] S2: The sulfide asphalt is polymerized at a temperature of 450°C and a pressure of 0.2 MPa for 5 hours to obtain a polymerization intermediate; the polymerization intermediate is then coked at 500°C to obtain high-sulfur raw coke.
[0080] S3: The high-sulfur raw coke is crushed to a particle size of D50=10.0 μm, and then graphitized at 2800° C. to obtain a graphite negative electrode material.
[0081] Example 7
[0082] A graphite negative electrode material is prepared by the following steps:
[0083] S1: 80 parts of medium-high sulfur asphalt, 17 parts of aromatic oil, and 3 parts of thiophene are mixed and heat-treated at 130°C to obtain sulfided asphalt. The sulfur content of the medium-high sulfur asphalt is 4% and the softening point is 50°C.
[0084] S2: The sulfide asphalt is polymerized at a temperature of 450°C and a pressure of 0.2 MPa for 5 hours to obtain a polymerization intermediate; the polymerization intermediate is then coked at 500°C to obtain high-sulfur raw coke.
[0085] S3: The high-sulfur raw coke is crushed to a particle size of D50=10.0 μm, and then graphitized at 2800° C. to obtain a graphite negative electrode material.
[0086] Example 8
[0087] A graphite negative electrode material is prepared by the following steps:
[0088] S1: 80 parts of medium-high sulfur asphalt, 17 parts of aromatic oil, and 3 parts of thiophene are mixed and heat-treated at 130°C to obtain sulfided asphalt. The sulfur content of the medium-high sulfur asphalt is 5% and the softening point is 50°C.
[0089] S2: The sulfided asphalt is polymerized at a temperature of 450°C and a pressure of 0.2 MPa for 5 hours to obtain a polymer intermediate; the polymer intermediate is then coked at 500°C to obtain high-sulfur raw coke.
[0090] S3: The high-sulfur raw coke is crushed to a particle size of D50=10.0 μm, and then graphitized at 2800° C. to obtain a graphite negative electrode material.
[0091] Example 9
[0092] A graphite negative electrode material is prepared by the following steps:
[0093] S1: 80 parts of medium-high sulfur asphalt, 17 parts of aromatic oil, and 3 parts of thiophene are mixed and heat-treated at 130°C to obtain sulfided asphalt. The sulfur content of the medium-high sulfur asphalt is 3% and the softening point is 60°C.
[0094] S2: The sulfide asphalt is polymerized at a temperature of 450°C and a pressure of 0.2 MPa for 5 hours to obtain a polymerization intermediate; the polymerization intermediate is then coked at 500°C to obtain high-sulfur raw coke.
[0095] S3: The high-sulfur raw coke is crushed to a particle size of D50=10.0 μm, and then graphitized at 2800° C. to obtain a graphite negative electrode material.
[0096] Example 10
[0097] A graphite negative electrode material is prepared by the following steps:
[0098] S1: 80 parts of medium-high sulfur asphalt, 17 parts of aromatic oil, and 3 parts of thiophene are mixed and heat-treated at 130°C to obtain sulfided asphalt. The sulfur content of the medium-high sulfur asphalt is 3% and the softening point is 80°C.
[0099] S2: The sulfide asphalt is polymerized at a temperature of 450°C and a pressure of 0.2 MPa for 5 hours to obtain a polymerization intermediate; the polymerization intermediate is then coked at 500°C to obtain high-sulfur raw coke.
[0100] S3: The high-sulfur raw coke is crushed to a particle size of D50=10.0 μm, and then graphitized at 2800° C. to obtain a graphite negative electrode material.
[0101] Embodiment 11
[0102] A graphite negative electrode material is prepared by the following steps:
[0103] S1: 80 parts of medium-high sulfur asphalt, 17 parts of aromatic oil, and 3 parts of thiophene are mixed and heat-treated at 130°C to obtain sulfided asphalt. The sulfur content of the medium-high sulfur asphalt is 3% and the softening point is 50°C.
[0104] S2: The sulfide asphalt is polymerized at a temperature of 450°C and a pressure of 0.2 MPa for 5 hours to obtain a polymerization intermediate; the polymerization intermediate is then coked at 500°C to obtain high-sulfur raw coke.
[0105] S3: The high-sulfur raw coke is crushed to a particle size of D50=9.0 μm, and then graphitized at 2800° C. to obtain a graphite negative electrode material.
[0106] Example 12
[0107] A graphite negative electrode material is prepared by the following steps:
[0108] S1: 80 parts of medium-high sulfur asphalt, 17 parts of aromatic oil, and 3 parts of thiophene are mixed and heat-treated at 130°C to obtain sulfided asphalt. The sulfur content of the medium-high sulfur asphalt is 3% and the softening point is 50°C.
[0109] S2: The sulfide asphalt is polymerized at a temperature of 450°C and a pressure of 0.2 MPa for 5 hours to obtain a polymerization intermediate; the polymerization intermediate is then coked at 500°C to obtain high-sulfur raw coke.
[0110] S3: The high-sulfur raw coke is crushed to a particle size of D50=12.0 μm, and then graphitized at 2800° C. to obtain a graphite negative electrode material.
[0111] Embodiment 13
[0112] A graphite negative electrode material is prepared by the following steps:
[0113] S1: 80 parts of medium-high sulfur asphalt, 17 parts of aromatic oil, and 3 parts of thiophene are mixed and heat-treated at 130°C to obtain sulfided asphalt. The sulfur content of the medium-high sulfur asphalt is 3% and the softening point is 50°C.
[0114] S2: The sulfide asphalt is polymerized at a temperature of 450°C and a pressure of 0.2 MPa for 5 hours to obtain a polymerization intermediate; the polymerization intermediate is then coked at 500°C to obtain high-sulfur raw coke.
[0115] S3: The high-sulfur raw coke is crushed to a particle size of D50=15.0 μm, and then graphitized at 2800° C. to obtain a graphite negative electrode material.
[0116] Embodiment 14
[0117] A graphite negative electrode material is prepared by the following steps:
[0118] S1: 80 parts of medium-high sulfur asphalt, 17 parts of aromatic oil, and 3 parts of thiophene are mixed and heat-treated at 130°C to obtain sulfided asphalt. The sulfur content of the medium-high sulfur asphalt is 3% and the softening point is 50°C.
[0119] S2: The sulfide asphalt is polymerized at a temperature of 450°C and a pressure of 0.2 MPa for 5 hours to obtain a polymerization intermediate; the polymerization intermediate is then coked at 500°C to obtain high-sulfur raw coke.
[0120] S3: The high-sulfur raw coke is crushed to a particle size of D50=7.0 μm, and then graphitized at 2800° C. to obtain a graphite negative electrode material.
[0121] Embodiment 15
[0122] A graphite negative electrode material is prepared by the following steps:
[0123] S1: 80 parts of medium-high sulfur asphalt, 16 parts of aromatic oil, and 4 parts of thiophene are mixed and heat-treated at 130°C to obtain sulfided asphalt. The sulfur content of the medium-high sulfur asphalt is 3% and the softening point is 50°C.
[0124] S2: The sulfide asphalt is polymerized at a temperature of 450°C and a pressure of 0.2 MPa for 5 hours to obtain a polymerization intermediate; the polymerization intermediate is then coked at 500°C to obtain high-sulfur raw coke.
[0125] S3: The high-sulfur raw coke is crushed to a particle size of D50=10.0 μm, and then graphitized at 2800° C. to obtain a graphite negative electrode material.
[0126] Comparative Example
[0127] A graphite negative electrode material is prepared by the following steps:
[0128] S1: Weigh 100 kg of artificial graphite, whose physical and chemical indicators are median particle size (D50) of 10 μm; weigh 4 kg of coal tar (softening point 220°C, secondary quinoline insoluble content of 14%); cross-put the artificial graphite and coal tar into a high-speed modified VC mixer and mix at a speed of 80 r / min for 180 min.
[0129] S2: After the mixing is completed, the mixture is placed in a graphitization furnace and heated to 420°C at a heating rate of 5°C / min under a nitrogen atmosphere. After being kept at this temperature for 2 hours, the mixture is heated to 1200°C at a heating rate of 20°C / min and kept at this temperature for 3 hours.
[0130] S3: The reactants are then cooled to room temperature and sieved through a 300-mesh vibrating sieving machine to obtain the graphite negative electrode material.
[0131] Test Example 1
[0132] The graphite negative electrode materials of Examples 1 to 15 and the comparative example were tested to detect the graphite interlayer spacing and grain size Lc. The test results are shown in Table 1.
[0133] Table 1 Test data of graphite negative electrode materials of embodiments and comparative examples project Graphite interlayer spacing (nm) Grain size Lc(nm) Example 1 0.33620 26.6 Example 2 0.33615 28.2 Example 3 0.33627 23.9 Example 4 0.33610 29.9 Example 5 0.33635 21.4 Example 6 0.33618 26.9 Example 7 0.33623 26.3 Example 8 0.33626 25.7 Example 9 0.33621 26.5 Example 10 0.33622 26.5 Embodiment 11 0.33624 26.4 Example 12 0.33618 26.8 Embodiment 13 0.33612 27.2 Embodiment 14 0.33629 26.1 Embodiment 15 0.33629 23.5 Comparative Example 0.33598 35.6
[0134] Test Example 2
[0135] The graphite negative electrode materials of Examples 1 to 15 and the comparative example were made into negative electrode sheets (specifically: the graphite negative electrode material, SP, CMC, and SBR were mixed and homogenized in a mass ratio of 94.0:3.0:1.0:2.0, and the negative electrode sheets were obtained through coating, drying, rolling and other processes), and then assembled with positive electrode sheets, electrolyte and other materials into 2Ah soft-pack batteries. The assembled soft-pack batteries were subjected to performance testing to test the rate performance and high-temperature storage performance of the batteries, and the test results are shown in Table 2.
[0136] The rate performance is the 2C / 0.5C capacity retention ratio, which is the ratio of the 2C charging capacity to the 0.5C charging capacity. The high temperature storage performance is the capacity retention ratio of the battery after being stored at 60°C for 100 days.
[0137] Table 2 Battery performance test data of the embodiment and the comparative example
[0138] From the data in Table 1 and Table 2, we can see that:
[0139] 1. Compare Examples 1 to 15 with the comparative example: From the data in Table 1, it can be seen that the graphite interlayer spacing of the graphite negative electrode materials of Examples 1 to 15 is not less than 0.33610 nm and is greater than the graphite interlayer spacing of the graphite negative electrode materials of the comparative example, and the grain size of the graphite negative electrode materials of Example 1 is not greater than 32 nm, and its grain size is relatively small, so the graphite negative electrode material prepared by the preparation method of the graphite negative electrode material of the present application has a small grain size and a large graphite interlayer spacing. From the data in Table 2, it can be seen that the rate performance of the battery prepared by the graphite negative electrode materials of Examples 1 to 15 is significantly better than the rate performance of the battery prepared by the graphite negative electrode materials of the comparative example, and the high temperature storage performance of the battery prepared by the graphite negative electrode materials of Examples 1 to 15 is also significantly better than the high temperature storage performance of the battery prepared by the graphite negative electrode materials of the comparative example.
[0140] Therefore, the graphite negative electrode material prepared by the method for preparing the graphite negative electrode material of the present application has a larger graphite layer spacing and a smaller grain size, which can significantly improve the rate performance and high-temperature storage performance of the prepared battery.
[0141] 2. Comparing Examples 1 to 5, it can be seen from Table 2 that the battery rate performance of Example 4 is slightly worse than that of Examples 1 to 3, and the high-temperature storage performance is slightly better than that of Examples 1 to 3. The battery rate performance of Example 5 is slightly better than that of Examples 1 to 3, and the high-temperature storage performance is slightly worse than that of Examples 1 to 3. It can be seen that increasing the amount of thiophene can improve the rate performance of the battery, but its high-temperature storage performance will decrease, and reducing the amount of thiophene will affect the rate performance of the battery. Therefore, the preferred amount of thiophene is 1 to 6 parts, and the most preferred amount of thiophene is 2 to 4 parts, so that the prepared battery has both good rate performance and high-temperature storage performance.
[0142] 3. Comparing Example 1 and Examples 11 to 14, it can be seen from Table 2 that the rate performance of the battery of Example 13 is worse than that of Example 1, Examples 11 and 12, and the high-temperature storage performance is better than that of Example 1, Examples 11 and 12. It can be seen that when the particle size D50 of the high-sulfur raw coke after crushing in step S3 is greater than 12.0 μm, although the high-temperature storage performance of the battery can be improved, its rate performance will decrease; the rate performance of the battery of Example 14 is better than that of Example 1, Examples 11 and 12, and the high-temperature storage performance is worse than that of Example 1, Examples 11 and 12. It can be seen that when the particle size D50 of the high-sulfur raw coke after crushing in step S3 is less than 9.0 μm, although the rate performance of the battery can be improved, its high-temperature storage performance will decrease; therefore, it is preferred to control the particle size D50 of the high-sulfur raw coke after crushing in step S3 to be between 9.0 μm and 12.0 μm, so that the prepared battery has both good rate performance and high-temperature storage performance.
[0143] So far, the technical solutions of the present application have been described in conjunction with the preferred embodiments, but it is easy for those skilled in the art to understand that the protection scope of the present application is obviously not limited to these specific embodiments. Without departing from the principles of the present application, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will fall within the protection scope of the present application.
Claims
1. A method for preparing a graphite negative electrode material, characterized in that: The preparation method comprises the following steps: S1: Aromatic oil, thiophene and medium-high sulfur asphalt are mixed and heat treated to obtain sulfided asphalt; S2: delaying coking the sulfided asphalt to obtain high-sulfur green coke; S3: crushing the high-sulfur raw coke, and then graphitizing it to obtain a graphite negative electrode material.
2. The method for preparing a graphite negative electrode material according to claim 1, characterized in that: The sulfur content of the medium-high sulfur asphalt is 2.5% to 5%, and the softening point of the medium-high sulfur asphalt is 50°C to 80°C.
3. The method for preparing a graphite negative electrode material according to claim 1, characterized in that: In step S1, the aromatic oil, the thiophene and the medium-high sulfur asphalt are added according to the following weight parts: 15-20 parts of aromatic oil, 1-6 parts of thiophene, and 76-83 parts of medium-high sulfur asphalt.
4. The method for preparing a graphite negative electrode material according to claim 3, characterized in that: In step S1, the weight proportion of thiophene is 2 to 4 parts.
5. The method for preparing a graphite negative electrode material according to claim 1, characterized in that: In step S1, the temperature of the heat treatment is 120°C to 160°C.
6. The method for preparing a graphite negative electrode material according to claim 1, characterized in that: Step S2 specifically includes: S21: polymerizing the sulfided asphalt at a temperature of 400° C. to 480° C. and a pressure of 0.1 MPa to 0.25 MPa to obtain a polymer intermediate; S22: subjecting the polymer intermediate to a coking reaction at 500° C. to 600° C. to obtain high-sulfur raw coke.
7. The method for preparing a graphite negative electrode material according to claim 6, characterized in that: In step S21, the polymerization time is 5h to 7h; And / or, in step S22, the coking reaction time is 16 hours to 20 hours.
8. The method for preparing a graphite negative electrode material according to claim 1, characterized in that: In step S3, the particle size of the high-sulfur green coke after crushing is D50=9.0 μm to 12.0 μm; And / or, in step S3, the temperature of the graphitization treatment is 2800°C to 3000°C.
9. A graphite negative electrode material, characterized in that: The graphite negative electrode material is prepared by the method for preparing the graphite negative electrode material according to any one of claims 1 to 8.
10. The graphite negative electrode material according to claim 9, characterized in that: The graphite layer spacing of the graphite negative electrode material is 0.3360nm-0.3364nm, and the grain size Lc of the graphite negative electrode material is 20.0nm-32.0nm.
Citation Information
Cited By
Sulfur-containing asphalt, composite materials, electrodes and batteries
CN122677448A
Sulfur-containing asphalt and evaluation methods, composite materials, electrodes and batteries
CN122677449A